Perception and Adoption of Soil Health Card by Paddy Growers of North Coastal Andhra Pradesh - CHUNDRU, RAMYA MADHURI; Akkamahadevi Naik; Ashok Kumar; Chitrasena Padhy; Soumik ray (Indian Journal of Extension Education, 2024)
The study examines the perception and adoption of Soil Health Card (SHC) practices among paddy growers in the North Coastal region of Andhra Pradesh for the years 2023-2024. The Soil Health Card Scheme, launched by the Indian government to support sustainable agriculture, provides farmers with tailored recommendations for crop-specific fertilizers,and detailed insights into soil nutrition and improve crop productivity. Despite its potential advantages, the extent of SHC adoption and its impact on paddy cultivation in this region remain insufficiently explored. Using a mixed-methods approach, the study combines quantitative surveys and qualitative interviews with paddy farmers who had Soil Health Cards across the North Coastal regions like Srikakulam and Vizianagaram districts. It examines factors influencing SHC perception and adoption, including demographic characteristics, awareness levels, and service accessibility. The research also evaluates the scheme’s effects on crop productivity, economic returns, and soil fertility management. Findings reveal that while many paddy growers have Soil Health Cards and (40%) report a moderate perception of the scheme, the actual adoption rate is relatively low at (43.8%). Barriers such as delays in card issuance and soil sample processing contribute to farmers’ reluctance to fully implement the scheme, despite their awareness of its benefits.